The Effect of Coloring Art Therapy on Academic Anxiety of Midwifery Final Year Students: Pengaruh Terapi Seni Mewarnai Terhadap Kecemasan Akademik Mahasiswa Tingkat Akhir Jurusan Kebidanan - Afidayani, Khairunnisa; Khairani, Wittin; Laasara, Nurun (Poltekkes Kemenkes Yogyakarta, 2023)
Academic anxiety is an impulse of thoughts and inner feelings that contain tension and fear, which results in disruption of thought patterns, physical responses, and behavior as a result of pressure in academic situations. Academic anxiety felt by students can affect their achievement index. One of the therapies that can be used to reduce academic tension is coloring art therapy, which can reduce anxiety levels and improve individual coping mechanisms. Objective of this research to heal the effect of coloring art therapy on the academic anxiety of final-year students of the Department of Midwifery, Poltekkes, Ministry of Health, Yogyakarta. This research is a pre-experimental design with a one-group pre-post-test design. Sampling technique with purposive sampling The sample used was the final-year students of the Midwifery Department, totaling 76 respondents. Statistical test using the Wilcoxon signed rank test. This study showed that 11% of students experienced mild anxiety, 68% experienced moderate anxiety, and 21% experienced severe anxiety based on the results of the pre-test scores. After coloring art therapy using the media